Pengaruh Teknik Baby Solus Per Aqua (Baby Spa) Terhadap Berat dan Panjang Badan Bayi 3-6 Bulan - Ade Kurniawati; Dewi Nurdianti; Ratni N (POLTEKKES KEMENKES MANADO, 2020)
Background: Infancy is a period where growth and development occur rapidly in children. One way to stimulate growth and development in children is by using the baby solus per aqua (SPA) technique which is done by heating, swimming and massage. Purpose: This study was to determine the effect of giving a baby spa on the increase in body weight and body length in infants 3-6 months. Methods: This study is a quasi-experimental study design with a one group pre-posttest research design. The sampling technique used was purposive sampling of 20 infants aged 3-6 months at Madre and Marwah Baby SPA Clinic. Baby Spa was carried out once a week for 4 times, data analysis used a paired t-test. Results: The study found that there was an effect of baby spa on body weight and there was an effect of baby spa on body length. As a recommendation for mothers of babies under five to regularly do a baby spa, so that the baby's growth will be maximized.